Childhood cutaneous vasculitis : A comprehensive appraisal - Palit Aparna; Inamadar Arun (Wolters Kluwer Medknow Publications, 2009)
Cutaneous vasculitides in childhood are rare and often present with clinical features distinct from adults. Diagnosis of cutaneous vasculitides in children was difficult because of lack of a satisfactory classification systems for this age group. A new international classification system for childhood vasculitis has been discussed in the following section along with important clinical features, diagnostic modalities, and recent therapeutic developments of important vasculitides in children.